Konsep Ma'rifat Dalam Matnul Hikam Karya Syaikh Ibnu Atho'illah - Nining Khurrotul Aini (Pena Islam Jurnal Pendidikan Agama Islam, 2021)
Ma'rifat in terms of language is the base for knowing or knowing, that is, knowing or knowing Allah by paying attention to all of his creation all the potential of reason and inner and outer. With ma'rifat to Allah, the human conscience will always be close to Allah SWT, the relationship between the heart and the members of the body is like a king against his servant, or like a leader of the people he leads. He is accepted by Allah when he is free and clean from it apart from Allah. And he will be prevented from God when he is busy and drowning with it besides Allah. They were warned that they would be asked, who to talk to and who to criticize if they were violated. He will be happy and fortunate because of his close relationship with God and cleanliness. On the other hand, it is the heart to be humiliated, ridiculed and abused, if it is dirty, full of stains, and sins